2016
DOI: 10.1007/s11605-016-3089-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardia and Non-Cardia Gastric Cancer Have Similar Stage-for-Stage Prognoses After R0 Resection: a Large-Scale, Multicenter Study in China

Abstract: Although the clinicopathological features of cardia gastric cancer (GC) differ from those of non-cardia GC, it is unclear whether the former has poorer prognosis than the latter. The aim of this study was to compare clinicopathological characteristics and prognosis between cardia and non-cardia GC. From December 2009 to December 2011, 1633 patients who had undergone R0 resection of GC at four Chinese centers were enrolled in this study. Their clinicopathological features and survival outcomes were evaluated. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
0
23
1
2
Order By: Relevance
“…In contrast to the findings of the present study, which found a similar prognosis in non-cardia adenocarcinoma and cardia adenocarcinoma during the last study period, the majority of existing data globally, indicate a clearly lower 5-year survival for gastric cardia adenocarcinoma compared to gastric non-cardia adenocarcinoma. 13 , 27 , 28 This discrepancy might be at least partly explained by the fact that the present study included a more recent time period than earlier studies. With a continued unchanged survival for gastric non-cardia adenocarcinoma and increasing survival for cardia adenocarcinoma, the reported survival rates will eventually become more equal also in other studies examining more recent data.…”
Section: Discussioncontrasting
confidence: 60%
“…In contrast to the findings of the present study, which found a similar prognosis in non-cardia adenocarcinoma and cardia adenocarcinoma during the last study period, the majority of existing data globally, indicate a clearly lower 5-year survival for gastric cardia adenocarcinoma compared to gastric non-cardia adenocarcinoma. 13 , 27 , 28 This discrepancy might be at least partly explained by the fact that the present study included a more recent time period than earlier studies. With a continued unchanged survival for gastric non-cardia adenocarcinoma and increasing survival for cardia adenocarcinoma, the reported survival rates will eventually become more equal also in other studies examining more recent data.…”
Section: Discussioncontrasting
confidence: 60%
“…A series of studies investigated the differences between cardia gastric cancer and non-cardia gastric cancer. They concluded that cardia gastric cancer patients were generally considered to have worse prognosis than the patients with non-cardia gastric cancer because of the different clinicopathological features [ 22 24 ]. In general, cardia gastric cancer was assumed to have more aggressive biological behavior and was more prone to lymph node metastasis and recurrence [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] After R0 resection, lymph node involvement has been demonstrated to be the most powerful prognostic factor for patients with resectable gastric cancer. [ 28 30 ] Accordingly, the UICC/AJCC TNM classification recommends that at least 15 lymph nodes should be retrieved for an adequate evaluation of the pN category of gastric cancer. [ 31 , 32 ] However, only 29% of gastric cancer patients have more than 15 lymph nodes dissected despite the AJCC/UICC guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 , 37 ] In addition, our other study also supported the idea that cardia and noncardia gastric cancer have similar stage-for-stage prognoses. [ 30 ] Moreover, ethnicity and geographic differences also influence the survival of patients with gastric cancer. For example, the 5-year survival rate in Romanian patients is less than 15%, whereas, in Japanese patients, it is 70%.…”
Section: Discussionmentioning
confidence: 99%